1988
DOI: 10.1136/bmj.297.6659.1317
|View full text |Cite
|
Sign up to set email alerts
|

Cervical screening in an inner city area: response to a call system in general practice.

Abstract: To determine whether a cervical screening call system based in general practice in a deprived inner city area would increase the numbers of women who came forward for cervical smears the response to letters of invitation for screening was monitored for one year in one general practice in the Paddington and North Kensington district of London. Women aged 20-64 were identified from the computerised age-sex register. Only 16% of these women had had a smear test. A total of 750 cali letters was sent out. Initially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1989
1989
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…A survey of non-responders indicated at least 20% incorrect addresses on the GMS register; this problem has also been found in other studies, particularly in inner cities 10,11 . Verification of addresses and identification of exclusions by GPs before issuing invitations was not satisfactory, and the scheduling and posting of invitations was also a problem.…”
Section: Discussionsupporting
confidence: 75%
“…A survey of non-responders indicated at least 20% incorrect addresses on the GMS register; this problem has also been found in other studies, particularly in inner cities 10,11 . Verification of addresses and identification of exclusions by GPs before issuing invitations was not satisfactory, and the scheduling and posting of invitations was also a problem.…”
Section: Discussionsupporting
confidence: 75%
“…Fifty people were interviewed and completed the questionnaire. Reasons given for non-response included ineligibility, having had a recent smear test (11), having had a hysterectomy (two), being men (three), or being a virgin (one). Other reasons included delayed intention to attend (11), not wanting a smear test (six), fear (seven), uncertainty about eligibility (seven), not having time (one), and never having thought about it (one).…”
Section: Resultsmentioning
confidence: 99%
“…However, when the strategy of mailed invitations was suspended, coverage fell to 61%, with older women being the most affected (Jensen and Birch, 1990). In our study, the best response was observed among women 50 to 64 years old, those who are at the greatest risk of invasive cervical cancer, but not of pre‐cancerous lesions (Shroff et al ., 1988). Furthermore, in most Latin American and Caribbean countries many women over 50 years of age have never undergone cervical cytology screening (Robles et al ., 1996).…”
Section: Discussionmentioning
confidence: 99%
“…For that purpose, multiple strategies have been suggested (Pontén et al ., 1995). Individual invitation, either by telephone or by mail, has been an effective recruitment mechanism in other countries (Hernández‐Peña et al ., 1997; Shroff et al ., 1988; Pierce et al ., 1989).…”
mentioning
confidence: 99%